The Sultan's renegades: Christian-European converts to Islam and the making of the Ottoman elite, 1575-1610 - Graf, Tobias (Oxford University Press, 2017)
'The Sultan's Renegades' inserts these 'foreign' converts into the context of Ottoman elite life to reorient the discussion of these individuals away from the present focus on their exceptionality, towards a qualified appreciation of their place in the Ottoman imperial enterprise and the Empire's relations with its neighbours in Christian Europe